(untitled) (Bangladesh Journal of Neuroscience, 2014)
Background: Back pain affects 60-80% of people at some time in their lives. Back pain is the most common cause of sickness-related work absence. Microwave diathermy could be an important treatment modality. Very few studies have been conducted in our country in this regard. Aims: To determine the effects of microwave diathermy in relieving symptoms of chronic low back pain when applied along with other conventional therapies like drug and exercise. Methods: Total 50 patients with chronic low back pain coming to OPD, DMCH were divided randomly into two groups and treated with nonsteroidal anti-inflammatory drugs, exercises, activities of daily living instructions and with or without microwave diathermy. Thereafter, the patients were evaluated weekly. After six weeks of treatment, improvements were observed in both the groups. Results: significant difference (P=0) in improvement was found in microwave diathermy group than in non-diathermy group. Conclusion: This study suggests that microwave diathermy is effective in treatment of patients with chronic low back pain. Bangladesh Journal of Neuroscience 2011; Vol. 27 (2) : 64-68 DOI: http://dx.doi.org/10.3329/bjn.v27i2.17544